An Overview on Pyranocoumarins: Synthesis and Biological Activities - Vlachou, Evangelia-Eirini N.; Litinas, Konstantinos E. (Current Organic Chemistry, 2019)
Pyrano- and dipyranocoumarins are classes of naturally occurring organic compounds with very interesting biological activities. This review focuses on the synthetic strategies for the synthesis of pyranocoumarins and dipyranocoumarins and the biological properties of those compounds. The synthesis involves the formation of the pyran ring, at first, from a coumarin or the formation of pyranone moiety from an existing pyran. Pyranocoumarins and dipyranocoumarins present anti-HIV, anti-cancer, neuroprotective, antidiabetic, antibacterial, antifungal, anti-inflammatory activities. Especially khellactones and calanolides are usually potent and selective in anti-HIV activity. Decursin and decursinol derivatives are effective as anticancer, neuroprotective, antidiabetic, antibacterial, and antifungal agents.
Keywords: calanolides